Effects of demersal trawling on marine infaunal, epifaunal and fish assemblages: studies in the southern Benguela and Oslofjord - Atkinson, Lara Jane (Department of Biological Sciences, 2014)
This thesis investigates the impacts of the demersal trawl fishery on infaunal, epifaunal and fish assemblages in the southern Benguela upwelling system for the first time. In the absence of representative areas of similar habitat protected from trawling in the southern Benguela region, infaunal and epifaunal assemblages were compared between heavily and lightly trawled areas to assess the impacts of the otter-trawl fishery. Infauna were sampled at four sites, from southern Namibia to near Cape Town by means of five replicate grab samples at each paired heavily and lightly trawled area. Invertebrate epifauna were sampled at two sites in heavily and lightly trawled areas using a finemeshed otter trawl. Sites ranged in depth from 350-450 m in unconsolidated sediment habitat. Epifaunal assemblages showed greater differences at heavily trawled areas with significantly reduced species diversity, average number of species and individuals. Several epifaunal species were absent from heavily trawled areas highlighting their vulnerability to impacts of trawling. Multivariate analyses show significant differences in composition of both infaunal and epifaunal assemblages among the sites and between trawling treatments at all sites. The results of this study suggest that intense trawling activities are at least partially responsible for significantly altering benthic community composition, affecting epifauna to a greater measurable extent than infauna. Biological Traits Analysis (BTA) was used to explore potential changes in ecological functioning of benthic assemblages, comparing areas exposed to heavy and light trawl intensities in the Benguela system. BTA incorporates biological traits (life-history, morphology and behaviour) of infaunal and epifaunal species with biomass, capturing a broad range of information of marine benthic assemblages. Seventeen percent of the infaunal traits analysed showed a significant difference between heavily and lightly trawled areas. Twenty-four percent of epifaunal biological traits investigated were significantly different between areas of heavy and light trawling. This study suggests that more intense trawling modifies some trait constituents of the benthic assemblage in the southern Benguela region, confirming the sensitivity of functional traits analysis in detecting changes induced by trawling disturbance. Biological traits analysis of benthic invertebrates shows promise as a practical technique for incorporation into monitoring programmes and for developing indicators of benthic ecosystem health, needed for implementation of an ecosystem approach to fisheries management in South Africa. A lack of representative untrawled areas in the trawl grounds of southern Africa precluded investigations comparing trawl impacts with unfished reference sites. A bilateral agreement between South Africa and Norway (NORSA) provided the opportunity to conduct experiments in an untrawled area of Oslofjord, Norway, where a shrimp trawl fishery for Pandalus borealis operates nearby. Infauna Abstract 2 were sampled at four untrawled sites in Oslofjord with five replicate grabs after which an Agassiz beam sled was dragged across two of the sites (impact sites) four times, simulating a trawl disturbance. Infauna were re-sampled at all four sites immediately after trawling (post-impact), 14 days and 64 days after the impact to monitor recovery of infaunal populations. Multivariate analyses comparing the impact sites with paired control sites for each sampling occasion showed no significant differences in infaunal assemblages at any stage of the experiment. Whilst it is considered possible that the trawl simulation was not a sufficient impact to represent that of a commercial trawl effect, it is considered more likely that trawl activities in Oslofjord do not inflict measurable impacts on infaunal assemblages. However, the impact of trawling on epifaunal assemblages in Oslofjord was not investigated in this study. Annual research survey data collected over the past 24 years (1986-2009) provide an opportunity to explore long-term demersal fish assemblage composition changes on the west coast of South Africa. Differences in spatial (latitude and depth) and temporal (seasonal and annual) factors were examined using multivariate analyses. Possible long-term changes were investigated using the Sequential T-test Algorithm to detect Regime Shifts (STARS). Results indicate geographic differences in fish assemblage composition from the northern to the southern region on the west coast of South Africa. The fish community composition is also clearly influenced by depth with a distinct change in fish assemblages in the shelf break region between 300 m and 400 m. Multivariate analyses also show two clear temporal changes in assemblage composition, firstly, in the early 1990s and secondly, in the mid- 2000s. STARS analyses detect long-term shifts in 27% of demersal species with the majority of speciesâ shifts detected either in the early- to mid-1990s or in the past decade (2002 to 2009). Multivariate analyses among year groups reveal an increase in three fast-growing, early maturing species and decreases in two slow-growing, long-lived species. STARS analysis detected increases in two of the same fast-growing species, decreases in an additional four slow-growing, long-lived species, but four other slow-growing, long-lived species showed the opposite trend (i.e. increases). The hypothesis of an increase in fast-growing, early maturing species and a decline in slow-growing, longlived species in fished systems is therefore only partially supported by these findings. Shifts in demersal fish assemblages coincide temporally with spatial shifts observed in small pelagic species and west coast rock lobster. The shifts in the demersal fish assemblage composition detected in this study are probably a reflection of long-term indirect effects of fishing in combination with environmental changes. Abstract 3 The response of benthic invertebrate assemblages to two levels of fishing intensity in the southern Benguela region justifies regular monitoring of epifauna during existing annual demersal research surveys and infaunal monitoring through dedicated, periodic sampling initiatives. Demersal fish assemblage data should be regularly assessed for changes in community composition. Representative protected areas can serve as reference areas against which fishing impacts could be assessed and improve our understanding of ecosystem effects of demersal fishing.